The Influence of Organizational Culture and Leadership Roles on Knowledge Sharing at PT. Thriveni - Akta Dia Nauly; Hamid Halin; Shafiera Lazuarni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to analyze the influence of organizational culture and the role of leadership on knowledge sharing at PT. Develop. This study uses a questionnaire as a tool in collecting basic data. This research was conducted at PT. Thriveni with a total of 54 respondents. Methods of data collection through questionnaires and analyzed using multiple linear regression. The results of the investigation show that partially Organizational Culture has a positive and significant effect on Knowledge Sharing. The Role of Leadership has a positive effect on Knowledge Sharing. Simultaneously, Organizational Culture and Leadership Role have a positive and significant effect on Knowledge Sharing.